1997
DOI: 10.2307/1592343
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Campylobacter spp. in Broilers: Source, Time of Colonization, and Prevalence

Abstract: From October 1993 to August 1994, broiler chickens in four grow-out houses, two previously used (houses 1 and 2) and two newly constructed (houses 3 and 4), were used in a study to determine the source, time of infection, and prevalence of Campylobacter spp. Cecal droppings and cecal samples were obtained from the broilers. Samples were also obtained from water, feed, litter, soil, fans, and workers' boots. Samples were obtained from domestic animals and wildlife species (rectal swabs), including insects, on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
102
2
8

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(122 citation statements)
references
References 18 publications
10
102
2
8
Order By: Relevance
“…In the United Kingdom and other European countries, where used litter is removed and houses are cleaned between flocks, longitudinal studies indicate that infection is not predictable from the Campylobacter status of the last flock in the house (26). Negative flocks often follow positive ones (6), and positive flocks can occur even in newly constructed broiler houses (37). There are no published reports of C. jejuni isolation from the floors and walls of emptied, cleansed, and disinfected houses (and many groups have searched).…”
Section: Sources Of Poultry Colonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United Kingdom and other European countries, where used litter is removed and houses are cleaned between flocks, longitudinal studies indicate that infection is not predictable from the Campylobacter status of the last flock in the house (26). Negative flocks often follow positive ones (6), and positive flocks can occur even in newly constructed broiler houses (37). There are no published reports of C. jejuni isolation from the floors and walls of emptied, cleansed, and disinfected houses (and many groups have searched).…”
Section: Sources Of Poultry Colonizationmentioning
confidence: 99%
“…Although such animals are unlikely to enter houses, they may excrete campylobacters in substantial numbers, and this can result in contamination of boots, other external clothing, and equipment taken into the houses. Certainly, genotypically identical strains can be found in cattle kept next to the broiler house and the broilers within the house (37,68), and the presence of other farm animals on the farms is a risk factor for flock colonization (35). Concrete aprons around houses that are regularly cleaned and disinfected, the enclosure of grazed areas, and restrictions on the freedom of movement of domestic pets should be effective measures to reduce these risks.…”
Section: Sources Of Poultry Colonizationmentioning
confidence: 99%
“…However, despite these documented outbreaks, Campylobacter continues to be a primarily sporadic disease (23). Campylobacters readily colonize poultry (9) and seem well adapted to the avian gut (4). This may partly explain the uphill battle of poultry farmers in the prevention of Campylobacter colonization of their flocks.…”
mentioning
confidence: 99%
“…Jones et al [18] reported that any contamination of insects was generally external not internal since C. jejuni was not isolated after disinfection of the external surfaces of insects and suggested that contamination of broilers may not originate from insects. Gregory et al [13] reported that no specific contamination source could be identified but there were some potential ones outside of broiler houses like rodents and wild birds. However, the source of C. jejuni infection to broilers is not clear.…”
mentioning
confidence: 99%